2007
DOI: 10.1088/0960-1317/18/1/017002
|View full text |Cite
|
Sign up to set email alerts
|

A capillary-pumped loop (CPL) with microcone-shaped capillary structure for cooling electronic devices

Abstract: A MEMS-based integrated capillary-pumped loop (CPL), which can be used for cooling electronic devices such as the CPU of a personal computer or notebook, was developed. The CPL consists of an evaporator and condenser both with the same size of 30 mm × 30 mm × 5.15 mm, which were fabricated using two layers of glass wafer and one layer of silicon wafer.A key element of the CPL is that the 480 ± 15 µm thickness silicon wafer where an array of 56 × 56 cone-shaped microholes that generates the capillary forces was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…As compared with a plain silicon wafer, their experiment demonstrated that the silicon chips of the same size integrated with rectangular and triangular micro heat pipe arrays charged with methanol could obtain reductions in the maximum temperature of 14.1 and 24.9°C as well as the temperature gradient of 11.4 and 16.2°C, respectively, at a power input of 4 W. The silicon-based micro heat pipe technology provides a promising alternative to the traditional cooling schemes and has attracted considerable attention [8][9][10][11]. Subsequently, research works on the development of micro capillary loops [12,13], micro radial grooved heat pipes [14], and micro loop heat pipes [15] in silicon chips were also reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As compared with a plain silicon wafer, their experiment demonstrated that the silicon chips of the same size integrated with rectangular and triangular micro heat pipe arrays charged with methanol could obtain reductions in the maximum temperature of 14.1 and 24.9°C as well as the temperature gradient of 11.4 and 16.2°C, respectively, at a power input of 4 W. The silicon-based micro heat pipe technology provides a promising alternative to the traditional cooling schemes and has attracted considerable attention [8][9][10][11]. Subsequently, research works on the development of micro capillary loops [12,13], micro radial grooved heat pipes [14], and micro loop heat pipes [15] in silicon chips were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…The pulsating heat pipe (PHP), a relatively new type of heat pipe characterized by excellent thermal performance [16], is also suitable for the miniaturization and integration with a chip in addition to aforementioned heat pipes [7][8][9][10][11][12][13][14][15]. The tube-type PHP, consisting of a capillary tube which is bent to form several parallel channels with the inner diameter of 1-5 mm, can effectively transfer heat from the hot end to the cold end through the chaotic slug/plug oscillating motion of working fluids in the meandering tube [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…By controlling the temperature in the compensation reservoir we control the operating temperature of the CPL (for instance, the saturation temperature in the evaporator wick) [5]. Due to this wide ability to adjust and control the operating temperature, CPL systems have become frequently used for heat collection in numerous heavily thermally loaded precise electronic devices, and not only in space industry [6][7][8][9]. Separating the compensation reservoir from the remaining part of the system makes the CPL more tolerant to heat loss, which facilitates its installation.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-devices and micro channel design have been of particular interest [16]. As an alternative, capillary driven exchangers have been studied where working fluid phase change is again the primary means of heat transfer [17][18][19][20][21][22]. Working fluids have varied, but were typically dependent on the expected temperature ranges of the final applications.…”
Section: Introductionmentioning
confidence: 99%